2016
DOI: 10.21272/jnep.8(3).03031
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on Structural and Mechanical Properties of Single-walled Carbon and Boron Nitride Nanotubes Functionalized with Carbenes

Abstract: This paper presents quantum chemistry study on structural and mechanical properties of a series of single-walled carbon nanotubes (SWCNTs) and boron nitride nanotubes (BNNTs) functionalized with carbenes. At the PBE/SVP level, the obtained data on pristine nanotubes are in good accordance with the results of previous experimental and theoretical studies. The calculations show that carbenes functionalization, in general, distorts both SWNCTs and BNNTs frameworks, but there exists the difference between 'axial' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
2
0
0
Order By: Relevance
“…Figure shows the calculated variations in total energy with volume for the two systems studied. For pure SWBNNT, the total energy decreased with volume from −268.05 to −268.35 eV and then varied directly with volume from 1400 a.u 3 , which is in accordance with the obtained experimental and theoretical data . A similar case was observed for the MoS 2 -doped SWBNNT, except that in this case, the volume is larger than the volume of pristine SWBNNT because the diameter increases as a result of MoS 2 doping.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Figure shows the calculated variations in total energy with volume for the two systems studied. For pure SWBNNT, the total energy decreased with volume from −268.05 to −268.35 eV and then varied directly with volume from 1400 a.u 3 , which is in accordance with the obtained experimental and theoretical data . A similar case was observed for the MoS 2 -doped SWBNNT, except that in this case, the volume is larger than the volume of pristine SWBNNT because the diameter increases as a result of MoS 2 doping.…”
Section: Resultssupporting
confidence: 88%
“…For pure SWBNNT, the total energy decreased with volume from −268.05 to −268.35 eV and then varied directly with volume from 1400 a.u 3 , which is in accordance with the obtained experimental and theoretical data. 21 A similar case was observed for the MoS 2 -doped SWBNNT, except that in this case, the volume is larger than the volume of pristine SWBNNT because the diameter increases as a result of MoS 2 doping. It was also found that MoS 2 impurity doping does not affect the mechanical stability of the optimized SWBNNT.…”
Section: Resultssupporting
confidence: 64%